Implementation of Health Education on Breast Care Techniques to Facilitate Breast Milk in Postpartum Mothers at the Army Hospital Kindergarten IV. 01 07 01 Pematangsiantar - Rantika Arin Dita; Riskawani Eka Putri Perangin-angin (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
Breast care is an act of massaging the back along the spine which is useful for facilitating breastfeeding, mothers are relaxed and comfortable in post partum mothers. The purpose of this study was to describe nursing care for post partum mothers with the application of back rolling massage to increase milk production. Respondents in this study were 2 people who were taken by purposive sampling technique. Data were collected by interview, physical examination, observation and documentation studies. The results of the assessment show that the client says the milk has not come out. The act of back rolling massage which is carried out for 3 days of treatment can increase milk production. The application of back rolling massage can overcome the problem of ineffective breastfeeding in post partum mothers. It is hoped that back rolling massage will be an alternative source in increasing breast milk production.